Kepuasan Buruh Perkebunan Kelapa Sawit Terhadap Keberlanjutan Program Kemitraan Inti Plasma - Irawan, Norbertus Citra; Suswadi, Suswadi; Mahananto, Mahananto (Manajemen Agribisnis: Jurnal Agribisnis, 2025)
The research problem addresses the level of satisfaction among palm oil plantation workers regarding the sustainability of the core plasma partnership program. This study is urgent due to the need to enhance workers' welfare and productivity, ensuring the program's long-term success. The research evaluates worker satisfaction across various attributes within the partnership framework. Using a quantitative and descriptive approach, the study was conducted purposively in Mesuji, Lampung, to understand the local context. Respondents were selected through snowball random sampling, totaling 60 participants. Data collection methods included surveys, interviews, and observations, analyzed using the Labor Satisfaction Index (LSI) Framework. The results show that workers are satisfied with labor standards compliance, clarity of rights, fairness in result distribution, and a conducive working environment. However, they are only moderately satisfied with clarity of obligations, empowerment, participation in decision-making, and capacity development.